2002
DOI: 10.1063/1.1485960
|View full text |Cite
|
Sign up to set email alerts
|

Localized relaxation in a glass and the minimum in its orientational polarization contribution

Abstract: The dielectric permittivity and loss spectra of the glassy state of 5-methyl-2-hexanol obtained by quenching it from the liquid state has been studied. In one experiment, the spectra were studied at different temperatures as the quenched sample was heated at 0.1 K/min from 105.3 to 160.5 K. In the second experiment, the quenched sample was heated from 77 to 131.6 K and kept at that temperature for 14.6 ks. The relaxation rate, f m,␤ , the dielectric relaxation strength, ⌬⑀ ␤ , and the distribution of relaxatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 52 publications
2
44
0
Order By: Relevance
“…1͑a͒ that the height of the Љ peak spontaneously decreases with time, as has been found in several earlier studies. These spectra were analyzed using the Novocontrol WINFIT program used previously 23,26 by fitting the real and imaginary parts of the equation for the complex permittivity,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1͑a͒ that the height of the Љ peak spontaneously decreases with time, as has been found in several earlier studies. These spectra were analyzed using the Novocontrol WINFIT program used previously 23,26 by fitting the real and imaginary parts of the equation for the complex permittivity,…”
Section: Resultsmentioning
confidence: 99%
“…In the earlier studies, 6,[8][9][10]23 it had been found that as a glass becomes denser on structural relaxation and its T f decreases, f m,JG does not change within the detection limits of the single frequency measurements and the dielectric spectra could not be determined in the required short time in those studies. 6,[8][9][10] It has now been found 12,20,24 that when a quenched sample structurally relaxes, f m,JG increases and ⌬ JG decreases.…”
Section: B Increase In the Relaxation Rate With Timementioning
confidence: 99%
See 2 more Smart Citations
“…Currently, four features of the ␣-relaxation process are regarded as characteristic of liquids; ͑i͒ It occurs with an asymmetric distribution of times, 5,6 which is interpreted in terms of dynamic heterogeneity; 7,8 ͑ii͒ the temperature dependence of its relaxation time follows a Vogel-Fulcher-Tammann type relation; [9][10][11] ͑iii͒ its dielectric relaxation strength increases on cooling; and ͑iv͒ its relaxation time is quantitatively related to the relaxation time of the Johari-Goldstein ͑JG͒ process, 12,13 which is the faster and localized motion whose occurrence leads to the large-scale diffusion involved in the ␣ relaxation, [14][15][16] and whose equilibrium dielectric properties show features that are characteristic of the ␣-relaxation process. 17 The dielectric relaxation time of the ␣-relaxation process is regarded as directly proportional to according to Maxwell's relation = / G ϱ , where G ϱ is the instantaneous shear modulus of the liquid. But recent studies have shown that G ϱ itself varies with the temperature, as the liquid's structure varies.…”
Section: Introductionmentioning
confidence: 99%